Consent recommendations for research and international data sharing involving persons with dementia. Issue 10 (3rd July 2018) - Thorogood, Adrian; Mäki‐Petäjä‐Leinonen, Anna; Brodaty, Henry; Dalpé, Gratien; Gastmans, Chris; Gauthier, Serge; Gove, Dianne; Harding, Rosie; Knoppers, Bartha Maria; Rossor, Martin; Bobrow, Martin; ,
Abstract: Consent is generally required for research and sharing rich individual‐level data but presents additional ethical and legal challenges where participants have diminished decision‐making capacity. We formed a multi‐disciplinary team to develop best practices for consent in data‐intensive dementia research. We recommend that consent processes for research and data sharing support decision‐making by persons with dementia, protect them from exploitation, and promote the common good. Broad consent designed to endure beyond a loss of capacity and combined with ongoing oversight can best achieve these goals. Persons with dementia should be supported to make decisions and enabled to express their will and preferences about participation in advance of a loss of capacity. Regulatory frameworks should clarify who can act as a representative for research decisions. By promoting harmonization of consent practices across institutions, sectors, and countries, we hope to facilitate data sharing to accelerate progress in dementia research, care, and prevention.